Assessing Systemic Trade Interconnectedness : An Empirical Approach - Massara, Alexander; Errico, Luca. (Washington, D.C. : International Monetary Fund, 2011)
The paper focuses on systemically important jurisdictions in the global trade network, complementing recent IMF work on systemically important financial sectors. Using the IMF's Direction of Trade Statistics (DOTS) database and network analysis, the paper develops a framework for ranking jurisdictions based on trade size and trade interconnectedness indicators using data for 2000 and 2010. The results show a near perfect overlap between the top 25 systemically important trade and financial jurisdictions, suggesting that these ought to be the focus of risk-based surveillance on cross-border spillovers and contagion. In addition, a number of extensions to the approach are developed that can provide a better understanding of trade dynamics at the bilateral, regional, and global levels.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Interconnectedness Ranking; Jurisdiction; Trade Sector; Trade; WP; China, People's Republic of